2021
DOI: 10.3390/ma14143874
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immediate Implantation and Provisionalization Combined with Guided Bone Regeneration by a Flap Approach in the Maxillary Esthetic Zone: A Retrospective Controlled Study

Abstract: The aim of this research was too compare the thickness change of labial contour and bone tissues, as well as some biological complications of immediate implantation with and without immediate provisionalization for a single anterior maxilla presenting a vertical defect on labial bone with the need of guided bone regeneration (GBR) by a flap approach. A total of 40 single implants were placed in 40 patients into fresh extraction sockets of the anterior maxilla with a vertical defect on the labial bone (<4 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…After 5 months, the newly formed bone was clinically evident, the implant was stable in position and CBCT revealed sufficient horizontal and vertical dimensions. A previous histological analysis revealed that xenografts can promote osteoblast proliferation in its porous structure, facilitating angiogenesis and early bone formation (27).…”
Section: Discussionmentioning
confidence: 99%
“…After 5 months, the newly formed bone was clinically evident, the implant was stable in position and CBCT revealed sufficient horizontal and vertical dimensions. A previous histological analysis revealed that xenografts can promote osteoblast proliferation in its porous structure, facilitating angiogenesis and early bone formation (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, guided surgery can be particularly challenging in esthetic zones due to severe labial bone resorption and vertical bone loss [ 1 ]. Consequently, implants are often placed based on the available bone envelope, which may compromise the emergence profile of the prosthesis and overall aesthetics.…”
Section: Introductionmentioning
confidence: 99%